UX of a Web based platform for market linkage between farmers and buyers in Tanzania - Mambile, Cesilia; Machuve, Dina; Moebs, Sabine (My University, 2018)
Poultry farming has a very good business potential (Mohammad Khairu Islam, Mohammed Forhad Uddin, 2014) since they are fast growing animals meaning the business has potential to generate high return on investment under a short period of time. For example past days it took about four months for a chicken to become two kilograms, however these days a two kilogram chicken can be produced within 42 days (Hamra, 2010). Despite the fact that poultry farming has good business potential there are some obstacles which hinder the poultry business success such as lack of market linkage. Even with advancement of technology which has brought affordable smartphones to most of the livestock farmers, potential livestock information systems in Tanzania are used by very few livestock farmers and some are not used at all (Mussa et al., 2016). It is not that users do not need the system, nor the system does not show any potential for them, but depend on its usability and how well it suited to the user requirements based on their differences. Users of the system have a lot of differences including exposure to technology (Kalimullah & Sushmitha, 2017). It is now as more important than ever that web applications provide a good user experience which was once considered luxury or an added expenses (Juan, 2014; Ross, 2014). Web based platform for reliable market linkage has been developed with more focus on usability and user experience design. Eye tracking method combined with retrospective think aloud method and facial expression was used to test user experience of the developed web application. The result shows that users were emotionally happy when performing the second and the third tasks. But when performing the first task and the last task users were emotionally anxiety and disappointed.
Supplemental Materials: https://osf.io/9qk56/
Keywords: UX; UX design; Web based platform; farmers and buyers; Market linkage; Marketinformation